Flow structure and characteristics in propeller jet-pile interaction - Celikoglu, Yesim; Yuksel, Yalcin; Guner, H. Anil Ari; Gurek, Batuhan; Bilmez, Yagizhan (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
This study experimentally investigates the hydrodynamic interaction between a propeller jet and a cylindrical pile, with particular emphasis on turbulence-driven bed shear stress amplification mechanisms. High-resolution, multi-plane, turbulence-resolving Particle Image Velocimetry (PIV) measurements are employed to obtain full-field velocity data, enabling spatial mapping of mean flow structures, direct estimation of Reynolds shear stresses, and detailed visualization of coherent vortex systems, including horseshoe, wake, and secondary vortices. Unlike previous studies relying primarily on point-wise Acoustic Doppler Velocimeter (ADV) measurements, the present approach provides a comprehensive characterization of turbulence structures governing near-bed stress distribution. A rigid rough-bed configuration is adopted to eliminate morphological feedback effects and isolate purely hydrodynamic modification mechanisms. A systematic baseline normalization framework is established by fully characterizing the no-pile propeller jet case and defining a reference shear stress under identical hydraulic conditions, allowing quantitative assessment of amplification and attenuation effects induced solely by the pile. Results indicate maximum bed shear stress amplification at theta approximate to 45 degrees, corresponding to angular positions of maximum scour depth reported in earlier experiments. Downstream shielding effects explain reduced erosion in wake regions, while asymmetric transverse turbulence structures account for asymmetric scour development. Furthermore, shear stress amplification attenuates with increasing pile-propeller separation distance, clarifying reduced scour severity under larger spacing configurations. The findings provide a turbulence-structure-based interpretation of propeller-induced scour processes, contributing to improved prediction and mitigation strategies for offshore and coastal infrastructure.
Keywords: Propeller jet; Turbulent shear stress; Particle image Velocimetry (PIV); Turbulence characteristics; Scour protection; Pile supported berthing port structures; SCOUR; Engineering; Oceanography